Examining Relationships between Physical Environments and Behaviors of Residents with Dementia in a Retrofit Special Care Unit. Issue 2 (18th January 2017) - Mobley, Christine; Leigh, Katharine; Malinin, Laura
ABSTRACT: Specialized Care Units (SCUs) in nursing home facilities offer care for individuals with late‐stage dementia primarily when care in the home no longer supports physical and sociobehavioral needs. Prior research has primarily examined new facilities; however, due to market demand and financial constraints, many SCUs are retrofits of existing nursing homes. The purpose was to determine the capacity of the physical environment to enhance person‐centered care (PCC) and identify potential design opportunities to help patients adapt to and cope with dementia progression to maintain quality of life (QoL). Grounded in empirical knowledge and best practices for SCU design, an instrumental case study of a retrofit SCU in the Rocky Mountain region of the United States examined relationships between the physical environment and the behavior of residents and staff. Qualitative and quantitative data were collected through a spatial inventory, staff e‐survey, and behavioral observations in the unit's public spaces. Data indicate that even (less than ideal) retrofit SCU designs have the potential to support PCC goals significantly, and some physical conditions found to undermine PCC goals could be remedied by simple (low‐cost) design interventions, suggesting staff may lack awareness of the capacity for the SCU physical environment to improve residents' QoL. By linking design features from empirical studies and best practices with observed behaviors in a retrofit SCU, the primary contribution of our exploratory study is a framework of roles design features play in adaptation–coping and maladjustment–stress for people managing progressive dementia conditions. This framework suggests directions for future research and evolving methods to better understand the impacts of environmental designs on users' QoL over the course of progressive illnesses, like dementia.